Decision Support System For Performance Assessment Of Village Equipment Using Hybrid Multi Criteria Decision Making (MCDM) Method Between AHP And TOPSIS (Bringin Village,Juwana Pati): Sistem Pendukung Keputusan Untuk Penilaian Kinerja Peralatan Desa Dengan Metode Hybrid Multi Criteria Decision Making (MCDM) Antara AHP Dan Topsis (Desa Bringin, Juwana, Pati) - Maulana, Muhdi; Handayani Untari N, Rr. Dewi (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
The Village Apparatus is a staff element that assists the Village Head in policy formulation and coordination, which is organized in the village secretariat and supporting the Village Head's duties in implementing policies, which are organized in the form of technical implementers and territorial elements. However, in reality, the performance of village officials in Bringin Village, Juwana Pati is still lacking and needs to be addressed in order to be optimal. Interviews conducted with the village head of Bringin, Juwana Pati said that the performance of village officials is still not considered optimal and good in a stable manner, so an evaluation is needed in the performance of village officials in Bringin Village, Juwana Pati. Therefore, a system is needed to evaluate, assess, and improve the performance of village officials in Bringin Village, Juwana Pati. The purpose of this study is to determine the results of the implementation of the Hybrid AHP and TOPSIS methods on a decision support system in helping the village head to conduct performance appraisals on village officials in Bringin Village, Juwana Pati. The system development method used is waterfall. The results of the implementation of the two methods concluded that the system built has been able to produce recommendations for determining the performance appraisal of village officials and meet functional needs. This shows that the AHP and TOPSIS methods can be used to solve problems related to determining the performance assessment of village officials by producing the best alternative based on the highest/largest preference value.